2016
DOI: 10.1021/acs.joc.6b00804
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Matrine-Type Alkaloids from the Roots of Sophora flavescens and Their Anti-Hepatitis B Virus Activities

Abstract: Six unusual matrine-type alkaloid dimers, flavesines A-F (1-6, respectively), together with three proposed biosynthetic intermediates (7-9) were isolated from the roots of Sophora flavescens. Compounds 1-5 were the first natural matrine-type alkaloid dimers, and compound 6 represented an unprecedented dimerization pattern constructed by matrine and (-)-cytisine. Their structures were elucidated by NMR, MS, single-crystal X-ray diffraction, and a chemical method. The hypothetical biogenetic pathways of 1-6 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 38 publications
(102 reference statements)
0
44
0
Order By: Relevance
“…As an alternative approach, natural products have provided great promises as potentially effective antiviral drugs. A broad spectrum of phytochemicals including flavonoids such as wogonin and polyphenolics such as geraniin has been isolated and investigated for antihepatitis virus activities in vitro as well as in vivo [ 87 , 88 ]. The underlying action mechanisms have been proposed mainly as prevention of virus entry, inhibition of viral antigen secretion, and suppression of DNA replication [ 89 ].…”
Section: The Potential and Mechanism Of Action Of Polyphenols In Tmentioning
confidence: 99%
“…As an alternative approach, natural products have provided great promises as potentially effective antiviral drugs. A broad spectrum of phytochemicals including flavonoids such as wogonin and polyphenolics such as geraniin has been isolated and investigated for antihepatitis virus activities in vitro as well as in vivo [ 87 , 88 ]. The underlying action mechanisms have been proposed mainly as prevention of virus entry, inhibition of viral antigen secretion, and suppression of DNA replication [ 89 ].…”
Section: The Potential and Mechanism Of Action Of Polyphenols In Tmentioning
confidence: 99%
“…Matrine, which was approved by Chinese FDA (CFDA) in 1995, is derived primarily from Sophora species plants and has a chemical formula of C 15 H 24 N 2 O (5). Matrine exhibits a wide range of pharmacological effects and has long been applied to treat viral hepatitis (6), neuropathic pain (7), isoproterenol-induced cardiotoxicity inflammatory and other diseases (8,9). In addition, increasing evidence has revealed that matrine displays anticancer effects in various cancers, such as gastric (10), rhabdomyosarcoma (11), acute myeloid leukemia (12), osteosarcoma (13), prostate (14), breast (15) and lung cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Matrine and its different derivatives were reported to have multiple effects in different disease models. For example, matrine can prevent bone loss [38], protect glial cells from central nervous system inflammation [39], alleviate intestinal inflammation [29], and decrease liver cell injury [40]. Additionally, it is reported that matrine showed very strong anti-tumor effect which includes cytotoxic effect on prostate tumor cells, bladder tumor cells, and breast cancer cells [31,41,42].…”
Section: Discussionmentioning
confidence: 99%